Phacoemulsification combined with High-Frequency Deep Sclerotomy (HDFS) in Primary Open Angle Glaucoma Patients in DR. Achmad Mochtar Bukittinggi Hospital: Oral Presentation - Observational Study - Ophthalmologist - YUSARDI, ROMI (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is the leading cause of irreversible blindness. Phacoemulsification-trabeculectomycombined procedure is performed for cataract and glaucoma patients. High-Frequency DeepSclerotomy is a minimally invasive surgical technique to control IOP in POAG. The study aims toinvestigate whether IOP can be significantly reduced by phacoemulsification-HDFS combinedprocedure. MethodsData were collected from August 2022 to March 2023 in this retrospective non-randomized study. Atotal of 20 eyes patient had undergone phacoemulsification combined with High-Frequency DeepSclerotomy (HDFS). Intraocular pressure (IOP) was measured before and after surgery on the firstday, 1, 2, 3 weeks, and 1st month postoperatively. ResultsAfter performing phacoemulsification combined with HDFS, the IOP was reduced from 29,87 mmHgto 16,67 mmHg, which is highly significant (p< 0,001). Mild hyphema is present in 1 (5%) case afterthe procedure. ConclusionHDFS combined with phacoemulsification is a potent surgical method that significantly reduces theIOP